Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/jacs.5b10440
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Intramolecular Asymmetric Allylic Dearomatization Reaction of Pyridines, Pyrazines, Quinolines, and Isoquinolines

Abstract: The first Ir-catalyzed intramolecular asymmetric allylic dearomatization reaction of pyridines, pyrazines, quinolines, and isoquinolines has been developed. Enabled by in situ formed chiral Ir-catalyst, the dearomatized products were isolated in high levels of yield (up to 99% yield) and enantioselectivity (up to 99% ee). It is worth noting that the Me-THQphos ligand is much more efficient than other tested ligands for the dearomatization of pyrazines and certain quinolines. Mechanistic studies of the dearomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(45 citation statements)
references
References 126 publications
2
42
0
Order By: Relevance
“…However, our recent research efforts demonstrated that electron-deficient arenes could also be involved in asymmetric allylic dearomatization reactions (Scheme 13). 45,46 In our mechanistic design plan, allylic carbonates 54 derived from pyridines, pyrazines, quinolines, and isoquinolines first react with chiral Ir catalyst to yield the corresponding p-allyliridium intermediates. The concomitantly generated methoxide anion abstracts the acidic a-proton in the substrates, making the nitrogen in the heterocycle a strong nucleophilic site as a result of the resonance of the negative charge (path a).…”
Section: Scheme 8 Ir-catalyzed Asymmetric Allylic Dearomatization Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our recent research efforts demonstrated that electron-deficient arenes could also be involved in asymmetric allylic dearomatization reactions (Scheme 13). 45,46 In our mechanistic design plan, allylic carbonates 54 derived from pyridines, pyrazines, quinolines, and isoquinolines first react with chiral Ir catalyst to yield the corresponding p-allyliridium intermediates. The concomitantly generated methoxide anion abstracts the acidic a-proton in the substrates, making the nitrogen in the heterocycle a strong nucleophilic site as a result of the resonance of the negative charge (path a).…”
Section: Scheme 8 Ir-catalyzed Asymmetric Allylic Dearomatization Ofmentioning
confidence: 99%
“…Ir-Catalyzed Asymmetric Allylic Dearomatization of Electron-Deficient Arenes Originally reported by the You group. 45,46 intermediate VI could be isolated or captured by in situ transformation. In addition, the synthetic utility of this reaction was also demonstrated by a facile synthesis of compound 56, which is a key intermediate in the synthesis of (+)-gephyrotoxin.…”
Section: Scheme 8 Ir-catalyzed Asymmetric Allylic Dearomatization Ofmentioning
confidence: 99%
“…A further direction of research was developed in the study of complexes of transition metals, such as Pd [23][24][25], Cu [26][27][28][29][30][31], Cu/Pd [32], Rh [33], Ir [34], Pt [35], Fe/Au [36], Sm [37], Ce [38], etc. They are used as catalysts for the derivation of pyrrolo[1,2-a]quinoline derivatives; however, despite their potential utility, none of these procedures can directly provide end products with a lack of heavy metal admixtures [39][40][41][42].…”
Section: Methodsmentioning
confidence: 99%
“…However,e nantiomerically pure small molecules have attracted increasing attention from medicinal chemists owing to their versatile interaction modes and tremendous potential in drug development. [11,12] However,t he successful cases were limited to six-membered-ring nitrogen-containing aromatic compounds,s uch as pyridines,p yrazines,q uinolines, and isoquinolines.T he dearomatization of five-memberedring Nheteroaromatic compounds had not been explored. [4] Meanwhile,dearomatized structures of benzoxazoles,benzothiazoles,a nd benzimidazoles are found as core skeletons in natural products (e.g.s trellidimine;S cheme 1) and biologically active small molecules (Scheme 1A-C).…”
mentioning
confidence: 99%
“…[5][6][7][8] During our research on the development of transitionmetal-catalyzed allylic dearomatization reactions, [9] which are ap owerful class of catalytic asymmetric dearomatization (CADA) reactions, [10] we recently realized iridium-catalyzed allylic dearomatization reactions of electron-deficient Nheteroaromatic compounds. [11,12] However,t he successful cases were limited to six-membered-ring nitrogen-containing aromatic compounds,s uch as pyridines,p yrazines,q uinolines, and isoquinolines.T he dearomatization of five-memberedring Nheteroaromatic compounds had not been explored. [13] Herein we report the successful application of the iridiumcatalyzed asymmetric allylic dearomatization strategy to various five-membered-ring nitrogen-containing aromatic compounds,i ncluding benzoxazoles,b enzothiazoles,a nd benzimidazoles.…”
mentioning
confidence: 99%